Stevens–Johnson syndrome and toxic epidermal necrolysis: a 10-year experience in a burns unit. (2nd June 2021) - Houschyar, Khosrow S; Tapking, Christian; Borrelli, Mimi R; Nietzschmann, Ina; Puladi, Behrus; Ooms, Mark; Rein, Susanne; Houschyar, Madeline; Duscher, Dominik; Maan, Zeshaan N; Reumuth, Georg; Branski, Ludwik K; et al.
Abstract : Objective: Stevens-Johnson syndrome (SJS) and its more severe counterpart, toxic epidermal necrolysis (TEN), are skin hypersensitivity reactions defined by epidermal blistering and necrosis. The exact pathophysiology of SJS/TEN is yet to be deciphered, but a number of risk factors have been identified including adverse drug reactions. The diagnosis of SJS/TEN is made on a clinical basis, and treatment consists of supportive care and occasionally immunosuppressants, such as cyclosporin, high-dose intravenous immunoglobulins and/or corticosteroids. Mortality rates can reach 20–25% in adults but are reduced with early intervention. To identify optimal treatment regimens, to better understand the patient cohort affected, and to help identify key risk factors for mortality, we report our experience with the treatment and management of SJS/TEN patients. Methods: A retrospective review of consecutive patients with SJS and/or TEN admitted to a single burns centre in Germany, between 2008 and 2018, was conducted. The primary outcomes of demographics, clinical course, treatment and patient-reported outcomes were recorded and compared with a control group of patients with burns without a diagnosis of SJS/TEN. Results: A total of 23 patients with SJS/TEN met the inclusion criteria: 17 (74%) with TEN; four (17%) with SJS/TEN overlap; and two (9%) with SJS. Of the patients, 14 (61%) were female and nine (39%) were male. Patient age ranged from 32–78 years (mean: 52 years). A matched cohort of 23 patients with burns served as the control group. All patients received standard of care with a multidisciplinary team. Compared with the control group, SJS/TEN patients had higher mortality rates (n=6, 26% versus n=8, 35%, respectively). The average age of death was 69 years in SJS/TEN patients versus 63 years in control group patients. Age and SCORTEN scores were significant predictors of mortality. Conclusions: SJS and TEN are rare but extreme reactions of the skin and mucosa, associated with high disease mortality rates. This 10-year single-centre retrospective review contributes to the bank of information for reviews evaluating the management of SJS/TEN patients.